IMPLEMENTASI KRIKULUM MERDEKA MANDIRI BERUBAH PADA PEMBELAJARAN SISWA KELAS V SD MUHAMMADIYAH 8 DAU - Zakiyah, Khalifatuz; Innany Mukhlishina; Ima Wahyu Putri Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Independent Independent Change curriculum is the curriculum chosen by SD Muhammadiyah 8 Dau in implementing the independent curriculum initiated by the Minister of Education and Culture, Nadiem Makarim. The objectives of this study are: (1) describe the planning of the independent independent curriculum in the learning of fifth grade students of SD Muhammadiyah 8 Dau, (2) describe the implementation of the independent independent curriculum in the learning of fifth grade students of SD Muhammadiyah 8 Dau, and (3) describe the evaluation of the independent independent independent curriculum in the learning of fifth grade students of SD Muhammadiyah 8 Dau. This research uses descriptive qualitative research methods. The data sources in this study took information from the principal, the head of curriculum, and the fifth grade teacher. The methods used to collect data are observation, interviews, documentation, and field notes. While the data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results showed (1) Planning for the Independent Self-Changing Curriculum in class V student learning begins with the teacher attending a work meeting in which there is training and coaching related to the independent self-changing curriculum. The school also utilizes the independent teaching platform as a learning resource and uses the materials contained in the independent teaching platform, but the design is left to each class teacher (2) Implementation of the Merdeka Independent Curriculum Changes in V grade student learning still does not optimally implement deferential learning (3) Evaluation of the Merdeka Curriculum in V grade student learning is carried out by the school in work meetings and evaluations in learning.